Thelastoma vanwaerebekei n. sp. (Oxyurida: Thelastomatidae) a parasite of Gymnetis litigiosa (Coleoptera: Scarabaeidae) from Uruguay - Orsini, María Noé Dambrosi; Cuellar, Natalia; Dueñas, Juan C. Rondan; Gardenal, Cristina N.; Doucet, Marcelo E.; Lax, Paola (Zootaxa, 2018)
Thelastoma vanwaerebekei n. sp. was extracted from the hindgut of Gymnetis litigiosa. The new species is included in the group of species with females having the excretory pore at the same level as the pharyngeal basal bulb (or slightly anteriorly), long tail length (approximately 30% of total body length) and males without spicules. Females of T. vanwaerebekei n. sp. differ from those of T. madecassum in tail shape (filiform and conical, respectively). They differ from T. basiri, T. imphalensis and T. dessetae in the morphology of the anterior region. In females, pharyngeal length is shorter than in T. depressum. In males, T. vanwaerebekei n. sp. differs from T. blabericola in the tail length, and from T. raoi in the number of caudal papillae. The partial 18S SSU and 28S LSU rRNA gene regions were amplified.